Podstawowe źródła kryzysów walutowych - Buszko, Andrzej (Basic Information of Currency Rate Crisis, 2005)
The article gives the basic information on the cause of currency crisis. The theoretical studies are compared with practical events in three different regions: Turkey, Thailand and Argentina. Those analyzes gave a clear picture on the way and reasons of crisis. Unfortunately they are not universal and cannot be adopted in any country. Thanks to this study two groups of reasons are indicated objective and subjective ones. The close attention is paid to currency crisis, connections with economic and particularly financial policy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 62-77